Increasing the energy efficiency and environmental safety of the operation of smallvolume furnaces by adding a water-fuel mixture and organic components - Kulagina Liudmila (E3S Web of Conferences, 2021)
Industrialisation is trending manufacturing revolution vector, an urgent task is to increase the energy efficiency and environmental safety of small-volume furnaces processes, which are widely applied in the agricultural industry, asphalt concrete plants, etc. In many countries, there are practically no working coal mines or open-pit mines left. However, in a number of regions, coal waste remained in the form of coal dust, ash or in the form of sludge. Utilization of coal dust by preparation of coal-water fuel (CWF) with subsequent combustion of the mixture is currently being applied as the most suitable method. The article discusses improvement of the technology for the preparation of coal-water fuel by applying the effects of hydrodynamic cavitation and adding waste from the livestock complex.